2019
DOI: 10.1111/jonm.12758
|View full text |Cite
|
Sign up to set email alerts
|

The self‐organizing map clustered registered nurses’ evaluations of their nurse leaders

Abstract: Aim To characterize registered nurses’ (RNs’) perceptions of nurse leaders’ transformational leadership (TL) qualities in Finnish university hospitals and identify predictors of positive and negative evaluations. Background Transformational leadership can improve health care but requires development. Information on TL is typically derived from survey results, which are vulnerable to confounders. Method Cross‐sectional survey. Registered nurses’ perceptions of nurse leaders were measured with the TL scale. Koho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…or other northern countries. Earlier studies showed that nursing personnel in Finland regard managers' transformational leadership qualities as moderate and their nurse directors as distant (5,6,7). The overall governance score in this study (203.6) places decision-making in the included hospitals within the PG spectrum (173-344) and roughly half or more of nearly all the included groups of nursing personnel felt that they had influence in nursing decisions.…”
Section: Nurses' Perceptions Of Involvement In Decisionmakingmentioning
confidence: 47%
See 2 more Smart Citations
“…or other northern countries. Earlier studies showed that nursing personnel in Finland regard managers' transformational leadership qualities as moderate and their nurse directors as distant (5,6,7). The overall governance score in this study (203.6) places decision-making in the included hospitals within the PG spectrum (173-344) and roughly half or more of nearly all the included groups of nursing personnel felt that they had influence in nursing decisions.…”
Section: Nurses' Perceptions Of Involvement In Decisionmakingmentioning
confidence: 47%
“…The results indicate that nursing personnel have access to information, influence over resources supporting their practice, control over their practice and ability to both set goals and resolve conflicts. This is encouraging for Finnish health care as a whole, and specifically the included university hospitals, which are actively developing their management style while pursuing Magnet status (7).…”
Section: Nurses' Perceptions Of Involvement In Decisionmakingmentioning
confidence: 94%
See 1 more Smart Citation
“…The working environment, physical and human resources, demands of work and structural dimensions including compensation, empowerment and schedule flexibility impact job satisfaction (Seitovirta et al, 2018; Yasin et al, 2020). Leadership is positively linked to job satisfaction (T. Kvist et al, 2012), particularly where leadership is transformational (Asif et al, 2019; T. Kvist et al, 2019; Morsiani et al, 2017). Leaders influence job satisfaction through organizational measures such as staffing (Al Sabei et al, 2020; Dilig‐Ruiz et al, 2018), empowerment (Asif et al, 2019; H. Li et al, 2018;), autonomy (Castaneda & Scanlan, 2014), decision‐making ability (T. Ylitörmänen et al, 2018), the ability to practice within one's full scope (Déry et al, 2018) and delivering quality patient care (Al Sabei et al, 2020; Asif et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…На сегодняшний день в медицинских исследованиях применяются нейронные сети разнообразной структуры. Используются нейросетевые самоорганизующиеся карты Кохонена [12,14, 24], сверточные нейронные сети [15,20,25], рекурентные нейронные сети [11,13,19], но классическим представителем такого рода моделей является многослойный перцептрон -полносвязная многослойная искусственная нейронная сеть прямого распространения [16,17,21].В отечественной биомедицинской литературе примеры применения нейронных сетей приведены при…”
unclassified